Faktor Pendukung dan Penghambat Implementasi Profil Pelajar Pancasila di Kelas IV SD Negeri Pesantren - Belita Yoan Intania; Tri Joko Raharjo; Arief Yulianto (Cetta: Jurnal Ilmu Pendidikan, 2023)
This study aims to describe the implementation of Pancasila class IV student profiles at SD Negeri Islamic Boarding Schools and the supporting and inhibiting factors for the implementation of Pancasila student profiles for class IV SD Negeri Pesantren. The research method used is a qualitative approach with a phenomenological research design. Data collection techniques used are observation, interviews, and documentation. The results of this study are as follows. Implementing the Pancasila Student Profile could be more optimal because of obstacles and problems. In the process of learning Pancasila education in class, teachers try to use various learning models in direct teaching that students can accept, involving students in emphasizing opportunities to consider values, reflection, and learning, which is usually the teacher and the curriculum. Second, the teacher's efforts to overcome obstacles and problems must try to approach students and make themselves role models for school members. Teachers can use the time to achieve the expected learning objectives, related to the limitations of learning media that can be replaced if students still have difficulty understanding the material, and create a comfortable and conducive classroom atmosphere by communicating and interacting with students.